Drug Delivery Nanoparticles in Skin Cancers. (2nd July 2014) - Dianzani, Chiara; Zara, Gian Paolo; Maina, Giovanni; Pettazzoni, Piergiorgio; Pizzimenti, Stefania; Rossi, Federica; Gigliotti, Casimiro Luca; Ciamporcero, Eric Stefano; Daga, Martina; Barrera, Giuseppina
Abstract : Nanotechnology involves the engineering of functional systems at nanoscale, thus being attractive for disciplines ranging from materials science to biomedicine. One of the most active research areas of the nanotechnology is nanomedicine, which applies nanotechnology to highly specific medical interventions for prevention, diagnosis, and treatment of diseases, including cancer disease. Over the past two decades, the rapid developments in nanotechnology have allowed the incorporation of multiple therapeutic, sensing, and targeting agents into nanoparticles, for detection, prevention, and treatment of cancer diseases. Nanoparticles offer many advantages as drug carrier systems since they can improve the solubility of poorly water-soluble drugs, modify pharmacokinetics, increase drug half-life by reducing immunogenicity, improve bioavailability, and diminish drug metabolism. They can also enable a tunable release of therapeutic compounds and the simultaneous delivery of two or more drugs for combination therapy. In this review, we discuss the recent advances in the use of different types of nanoparticles for systemic and topical drug delivery in the treatment of skin cancer. In particular, the progress in the treatment with nanocarriers of basal cell carcinoma, squamous cell carcinoma, and melanoma has been reported.